(untitled) (Web of Humanities: Journal of Social Science and Humanitarian Research, 2024)
Persistent defect, deficiency and changes in the anatomical structure of the heart; interferes with normal blood flow. A distinction is made between congenital and acquired heart disease. Congenital heart defects occur as a result of incorrect formation of the fetal heart and large vessels of the heart during embryonic development. In the early period of pregnancy, poisoning of the mother’s body, suffering from some diseases, biological effects of ionizing rays, hereditary diseases, etc. cause.